STATUS OF THE HIMALAYAN LYNX IN DISTRICT CHITRAL, NWFP, PAKISTAN - J. U. Din; M. A. Nawaz (Journal of Animal and Plant Sciences, 2010)
The Eurasian lynx, listed Near Threatened in IUCN Red List, has one of the widest ranges of all cat species. Its Himalayan populations are known to be distributed in northern Pakistan, including Chitral district. However, actual status of the species and its real distribution limits are not known in Pakistan. This study provides an assessment of the status and distribution of the Himalayan Lynx in Chitral District, NWFP along with intensity of its conflicts with humans. Lynx occurrence was confirmed through public reports and livestock depredation cases were documented in five tehsils of the district. One hundred and sixty-four reports of lynx occurrence and 214 incidents of livestock depredation were recorded from 2001-2008 in an area of 14,850km2 of the district. Highest reports were from the Mastuj and lowest from the Torkhow tehsil. Livestock especially sheep lambs and goat kids were the major victims of lynx attack followed by poultry. This livestock loss means an economic hardship for the poor communities, thus, is a major source of human-cat conflicts. The prime threats to the existence of carnivores were retaliatory killing, loss of natural prey-base, loss of habitat, overpopulation, and lack of awareness and support.
Keywords: Chitral; Depredation; Himalayan Lynx; Population; Status